The role of individual differences in second language development in a study abroad context - İşlek, Coşkun. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This study investigated the effectiveness of Study Abroad (SA) in the development of learners in oral and written accuracy, and grammatical knowledge. A second concern was whether individual differences, namely motivation, aptitude, language contact, and initial proficiency, influence how much learners gain in accuracy and grammatical knowledge in the SA program. To these ends, the language development of 41 high school learners of English from Turkey in a 10-month-long exchange program in the USA was observed. These participants were given descriptive essay and oral narrative tasks, and a Grammatical Judgment Test task prior to and following their SA experience, once immediately before they returned to Turkey and another two months after their return. Other measures used to assess individual differences included a Language Aptitude Test, a motivation questionnaire, the English Language Test for International Students, Language Contact Profile and student diary entries. The participants made significant progress in their accuracy in both oral and written tests, and their grammatical knowledge. The results suggested that individual differences like aptitude for grammatical inferencing and vocabulary learning can partially explain L2 gains, especially for oral accuracy development. Another individual difference was sustained language contact opportunities after the study abroad was completed. Initial proficiency and motivation, however, did not explain the variances in L2 development. This study discusses these findings in relation to the participant profile.
Keywords: Second language acquisition.